2018
DOI: 10.1371/journal.pone.0206601
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of circulating cell-free DNA (cfDNA) in a newborn piglet model of perinatal asphyxia

Abstract: Perinatal asphyxia is a severe medical condition resulting from oxygen deficiency (hypoxia) at the time of birth, causing worldwide approximately 680,000 newborn deaths every year. Better prediction of severity of damages including early biomarkers is highly demanded. Elevated levels of circulating cell-free DNA (cfDNA) in blood have been reported for a range of different diseases and conditions, including cancer and prematurity. The objective of this study was to validate methods for assessing cfDNA in blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 74 publications
(106 reference statements)
0
20
0
Order By: Relevance
“…(2011) found that variations of absolute DNA values were mainly caused by the use of different isolation methods, with MagNA Pure isolation system (Roche Diagnostics, Mannheim, Germany) yielding highest DNA concentration [31]. We have previously tested different cfDNA isolation kits for blood samples collected from piglets, including the DNeasy Blood & Tissue Kit from Qiagen, NucleoSpin Plasma XS Kit from Macherey-Nagel, and Wizard Genomic DNA Purification Kit from Promega [11]. All the tested methods resulted in very low amounts of cfDNA and we suggested that a direct method for cfDNA isolation should be applied in the future.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(2011) found that variations of absolute DNA values were mainly caused by the use of different isolation methods, with MagNA Pure isolation system (Roche Diagnostics, Mannheim, Germany) yielding highest DNA concentration [31]. We have previously tested different cfDNA isolation kits for blood samples collected from piglets, including the DNeasy Blood & Tissue Kit from Qiagen, NucleoSpin Plasma XS Kit from Macherey-Nagel, and Wizard Genomic DNA Purification Kit from Promega [11]. All the tested methods resulted in very low amounts of cfDNA and we suggested that a direct method for cfDNA isolation should be applied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that cfDNA levels in plasma could reflect hypoxic changes in the brain [11], which was based on previous observations of higher concentrations of circulating cfDNA in premature neonates [10]. However, cfDNA is not only present in blood, it has been found in other body fluids, including cerebrospinal fluid (CSF) and urine [11,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations